TiO2 Nanotube Layers Decorated with Al2O3/MoS2/Al2O3 as Anode for Li-ion Microbatteries with Enhanced Cycling Stability - Tesfaye, Alexander Teklit; Sopha, Hanna; Ayobi, Angela; Zazpe, Raul; Rodriguez-Pereira, Jhonatan; Michalicka, Jan; Hromadko, Ludek; Ng, Siowwoon; Spotz, Zdenek; Prikryl, Jan; Macak, Jan M; Djenizian, Thierry (Nanomaterials (Basel, Switzerland), 2020)
TiO2 nanotube layers (TNTs) decorated with Al2O3/MoS2/Al2O3 are investigated as a negative electrode for 3D Li-ion microbatteries. Homogenous nanosheets decoration of MoS2, sandwiched between Al2O3 coatings within self-supporting TNTs was carried out using atomic layer deposition (ALD) process. The structure, morphology, and electrochemical performance of the Al2O3/MoS2/Al2O3-decorated TNTs were studied using scanning transmission electron microscopy, energy dispersive X-ray spectroscopy, X-ray photoelectron spectroscopy, and chronopotentiometry. Al2O3/MoS2/Al2O3-decorated TNTs deliver an areal capacity almost three times higher than that obtained for MoS2-decorated TNTs and as-prepared TNTs after 100 cycles at 1C. Moreover, stable and high discharge capacity (414 µAh cm-2) has been obtained after 200 cycles even at very fast kinetics (3C).
Keywords: Al2O3; Li-ion microbatteries; MoS2; TiO2 nanotube; atomic layer deposition